Grantchester. The complete eighth season [videorecording (DVD)] - Coulam, Daisy (Masterpiece theatre (Television program), 2023)
Will's life has changed for the better. He is happily married to the brilliant Bonnie and due to become a father, but his world is about to be rocked by a terrible accident. He's always preached the word of a compassionate God, but how can he do that now?